Effect of surrounding vegetation on edge-related tree mortality in Amazonian forest fragments - Mesquita, Rita de Cássia Guimarães; Delamônica, Patricia; Laurance, William F. (Biological Conservation, 1999)
Little is known about factors that cause spatial variability in edge effects, the diverse physical and biotic changes associated with the abrupt boundaries of fragmented forests. We examined the influence of three types of surrounding vegetation (cattle pastures, Cecropia-dominated regrowth, and Vismia-dominated regrowth), on edge-related tree mortality in Amazonian rainforest fragments. An ANCOVA revealed that the type of surrounding vegetation and distance to edge both had significant effects on tree mortality. Differences among vegetation types were greatest within 0-20 m of fragment edges, with edges bordered by cattle pastures having higher mortality than those bordered by Cecropia- and Vismia-dominated regrowth. Edge effects appeared to penetrate further into pasture-bordered edges (ca. 60-100 m) than those bordered by regrowth forest (ca. 40-60 m), but this difference was nonsignificant because of considerable patchiness in tree mortality. Overall, our results suggest that edge effects in forest fragments are significantly influenced by the structure of surrounding vegetation, and that the capacity of different regrowth forests to buffer edge effects can be predicted from the growth form and stand features of the dominant tree species. Management of surrounding vegetation can ameliorate the negative effects of edge creation on small forest fragments.
Keywords: Edge Effect; Forest Edge; Habitat Fragmentation; Habitat Type; Mortality; Rainforest; Vegetation Structure; South America; Cecropia; Vismia